Decision Support System for Best Honorary Teacher Performance Assessment Using a Combination of LOPCOW and MARCOS - Putra, Ade Dwi; Arshad, Muhammad Waqas; Setiawansyah, Setiawansyah; Sintaro, Sanriomi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Teachers are the main pillars in the formation and development of future generations. They not only pass on knowledge, but also play an important role in guiding, inspiring, and shaping the character of students. The main problems in selecting the best honor teachers are limited resources and a less systematic evaluation process, lack of transparency and consistency in the selection process can also lead to dissatisfaction and injustice among honor teachers. Through the combination of LOPCOW and MARCOS, this research succeeded in producing a more accurate and accountable ranking in the selection of the Best Honorary Teacher. The LOPCOW approach provides a deep understanding of percentage changes against set criteria, while MARCOS assists in weighting compromise solutions that can optimally meet those criteria. Thus, the study provides a more holistic and detailed view of various aspects of teacher quality and performance, enabling better decision-making in selecting the Best Honorary Teachers who meet educational needs and advance student learning. The ranking results showed that the assessment results from the LOPCOW and MARCOS methods gave results, namely rank 1st with a final value of 0.3404446 obtained by SF Teachers, 2nd place with a final value of 0.3367384 obtained by LBS Teachers, and 3rd place with a final value of 0.3343083 obtained by ASB Teachers.